Indonesia-Malaysia Border Conflict - Aos Y. Firdaus; Harun Umar (SIASAT, 2022)
Border management is seen as less than optimal and integrated, especially on the Indonesia-Malaysia border. There are border areas that are still unfinished, starting from Sebatik, Nunukan, Sanggau, and Entikong. Nine points need to be resolved to strengthen the legitimacy of the borders of each country. The difficulty is that Malaysia and Indonesia have very close borders. The research question raised in this study is how to regulate legal and political policies in determining borders according to international law and managing the Indonesia-Malaysia land border area. The theory used in this research is the concept of borders and international law. This study uses a qualitative method and comprehensively describes the Indonesia-Malaysia border conflict resolution. The findings obtained from the study are that Indonesia, as a sizeable sovereign country, must continue to strive to resolve border conflicts so as not to disrupt relations between the two countries.